ANALISIS HUKUM PERANAN PEJABAT PEMBUAT AKTA TANAH DALAM PEMUNGUTAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN ATAS TRANSAKSI JUAL-BELI TANAH DAN BANGUNAN DI KABUPATEN HUMBANG HASUNDUTAN - NOVITA DAMERIA MARBUN (PREMISE LAW JURNAL, 2017)
The increase in the development in various fields triggers the need for land and buildings whereas they are very limited. Since land and buildings are very crucial for human life, it is natural if the acquistition of land and building is taxable with BPHTB (Duty on Land and Building Right Acquistion). The research problems were as follows: how about the regulation on BPHTB levying system on land and/or building transact, how about the regulation on the role of PPAT/Notary on BPHTB levying on land and building transact in Humbang Hasundutan Regency, and how about fulfilling the principle of justice in imposing sanction on PPAT in signing land and building transact with unpaid BPHTB in Humbang Hasundutan.Keywords: PPAT, BPHTB (Duty on Land and Building Right Acquisition), Transact